Surface and Cross-Sectional Morphology of Wood Plastic Composite Using Scanning Electron Microscopy - Kamaruzaman, Muhammad Hazim; Asman, Saliza (Enhanced Knowledge in Sciences and Technology, 2026)
The natural-fibre-reinforced polymer materials based on wood plastic composites (WPCs) are broadly utilized because they offer better performance in terms of stiffness, dimensional stability and environmental advantages. Microstructural features, including fibre dispersion, interfacial adhesion, and the creation of void, have a very significant impact on the performance of WPCs. This study evaluates the surface and cross-sectional morphology of a commercial polyvinyl chloride (PVC)-based WPC reinforced with 40% wood fibre. Characterization was performed using Scanning Electron Microscopy (SEM) combined with Energy Dispersive X-ray Spectroscopy (EDS) to qualitatively analyze surface elemental composition. SEM measurements showed an anisotropic and non-uniform surface morphology that was exposed to the wood fibres and micro-voids. Cross-sectional observations showed heterogeneous fibre distribution, interfacial gaps and internal voids in the cross-section, which indicated the incomplete polymer encapsulation and low fibre-matrix compatibility. Analysis on the surface through EDS revealed the presence of carbon and oxygen peaks that are predominantly in the polymer matrix and lignocellulosic fibres respectively and several inorganic elements that are linked to natural fibre components and polymer additives. All in all, the findings indicate that morphological characteristics on the surface and inside are directly connected with the quality of WPC materials and the interfacial bonding, dispersing of the fibres, and the optimum processing condition play a significant role in creating high-quality wood plastic composites.